Does draft currency promote competitive balance? An empirical investigation of the National Football League 2002-2021 - Lapré, M. A.; Palazzolo, E. M. (Journal of Sports Economics, 2024)
In the National Football League (NFL) annual draft, teams take turns selecting entering players. The draft is a market mechanism designed to promote competitive balance as the NFL assigns draft positions to teams in reverse order relative to last season's performance. Teams frequently trade draft picks for other picks and/or players. We use several market valuations of draft picks to define original draft currency as the total value of draft picks available before any trades and final draft currency as the total value of picks used after all trades. For the 2002-2021 period, we find that original draft currency does not affect the probability of reaching the playoffs, but final draft currency does. Usage of outdated market valuations of draft picks by most teams can help explain how the best team has used draft-pick trades to remain among the strongest teams over two decades thereby perpetuating competitive imbalance.